Comoros Public Expenditure and Fiscal Management Review - World Bank (Washington, DC, 2017)
The objective of the Comoros public expenditure and fiscal management review is to assist the Government of Comoros in strengthening the basis for the management of its public expenditure program. The review takes stock of expenditure trends and the systems governing public spending, with an emphasis on strengthening fiscal sustainability, budget credibility and strengthening fiscal management in the electricity and service delivery sectors.